Res Medica, Spring 1963, Volume 3, Number 3 (Res Medica, 2013)
TABLE OF CONTENTSABDOMINAL CRISES III: I.S.R. Sinclair, F.R.C.S.THE BIOLOGY OF MONGOLISM: R.A. Bailey, M.B., Ch.B.RES MEDICASOME ASPECTS OF FUNCTIONAL ORGANISATION IN THE CEREBRAL CORTEX: D.G. Hardy, B.Sc.THE APPEAL FUNDCONGENITAL DISLOCATION OF THE HIP: P.J. Swarbrick, M.B., Ch.B.